A kind of water-based peelable coating and preparation method thereof
By using composite coating filler powder in water-based peelable coatings, the problems of insufficient surface hardness and poor impact resistance of existing coatings are solved, higher hardness and impact resistance are achieved, and the application effect of the coating is improved.
Patent Information
- Application Number
- CN202411157147.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The existing water-based peelable coatings have insufficient surface hardness, poor impact resistance, easy to break, and are prone to fall off or powder during long-term use, affecting the application effect.
Water-based silicone-modified acrylic emulsion is combined with composite coating filler powder, and the composite coating filler powder is prepared through click chemical reaction and epoxidation reaction to improve the hardness and impact resistance of the coating.
Significantly improves the surface hardness, impact resistance, salt water resistance and aging resistance of water-based peelable coatings, enhancing its application effect and scope of application.
Smart Images

Figure BDA0005005324850000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of coatings, and in particular to a water-based strippable coating and a preparation method thereof. Background Art
[0002] Some sensitive precision parts, instruments, meters and other equipment need to be protected and stored. Therefore, in order to reduce natural damage and extend the service life of the equipment, the equipment needs to be effectively sealed and protected, but the seal needs to be removed when it is needed. The use of a peelable protective film is the most effective and convenient way to solve this problem. Since the peelable protective film has no adverse effect on the surface of the protected object, it has a wide range of applications and can be used for indoor and outdoor, short-term and long-term protection of metal and non-metal materials. In addition, in the nuclear industry, peelable protective films are used to remove radioactive isotope contaminants from nuclear equipment. Due to its peelable characteristics, this protective film can also be used in some non-rust-proof occasions, such as as an insulating material in electroplating to protect the unplated parts.
[0003] Strippable coatings can be divided into two types: solvent-based and water-based latex. Solvent-based strippable coatings are coatings that use organic solvents as dispersants. This type of coating contains highly volatile organic solvents. The purpose of using these solvents is to allow the coating to dry quickly on the surface of the substrate without sagging. Therefore, solvent-based coatings have the advantage of short drying time. The addition of these fast-drying organic solvents can make the wet film thickness reach a certain thickness and can also make the solvent evaporate quickly in the natural environment to dry the coating. However, the use of a large amount of organic solvents in the coating not only seriously pollutes the environment, but is also harmful to the human body. Water-based strippable coatings are coatings that disperse polymer film-forming substances in water. Their biggest advantages are environmental protection and safety. Using cheap water instead of expensive and toxic organic solvents will not pollute the environment, but also save production costs and improve construction safety. However, most of the water-based strippable coatings on the market currently have insufficient surface hardness of the coating, and the coating is prone to breakage when impacted by external forces; in addition, some water-based strippable coatings will also fall off or powder during long-term use, thus affecting their application effect. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a water-based strippable coating and a preparation method thereof.
[0005] The purpose of the present invention is achieved by the following technical solutions:
[0006] In a first aspect, the present invention provides a water-based peelable coating, calculated by weight, comprising:
[0007] 67-84 parts of water-based silicone-modified acrylic emulsion, 8-16 parts of composite coated filler powder, 0.5-1 parts of dispersant, 1.1-2.3 parts of film-forming aid, 0.2-0.8 parts of thickener, 0.1-0.5 parts of leveling agent, 0.05-0.2 parts of defoamer and 10-20 parts of deionized water.
[0008] Preferably, the brand of the water-based silicone-modified acrylic emulsion is UC-3300 or UC-3500, and the manufacturer is Guangzhou Haoyi New Materials Technology Co., Ltd.
[0009] Preferably, the dispersant is at least one of BYK-191, BYK-103 and BYK-810.
[0010] Preferably, the film-forming aid is at least one of alcohol ester lauryl, propylene glycol butyl ether, and propylene glycol methyl ether acetate.
[0011] Preferably, the thickener is at least one of ACRYSOL RM-8W, ACRYSOL RM-12W, and ADEKANOL UH-420.
[0012] Preferably, the leveling agent is at least one of BYK-380N, BYK-330, BYK-333, and BYK-350.
[0013] Preferably, the defoaming agent is at least one of Dow Corning DC-65, Dow Corning DC-106F, Dow Corning ACP-1400, and Dow Corning AFE-1247.
[0014] Preferably, the preparation method of the composite coated filling powder comprises:
[0015] S1. Weigh 2,2'-diallyl bisphenol A and furfural into a reaction container, stir thoroughly, add alkali solution until the pH of the reaction solution is 8.5-9.5, heat to 170-180°C, keep the temperature under reflux for 2-3h, wash with water three times, and vacuum dry to obtain diallyl bisphenol A furfural resin;
[0016] S2, adding NH2-PEG-SH into tetrahydrofuran, after fully dissolving, then adding diallyl bisphenol A furfural resin, stirring until uniform, then adding a certain amount of photoinitiator, stirring reaction under irradiation of ultraviolet light, stirring time is 1-2h, stirring speed is 150-200r / min, after the reaction is completed, removing the solvent under reduced pressure to obtain NH2-PEG-furfural resin;
[0017] S3. Weigh tantalum disilicide powder and deionized water, mix them, add coupling agent KH-560 dropwise, reflux for 5-8 hours, filter and dry to obtain tantalum disilicide epoxide; add NH2-PEG-furfural resin into anhydrous ethanol, then add tantalum disilicide epoxide, heat to 60-80°C, keep warm and reflux for 3-6 hours, remove the solvent under reduced pressure to obtain a composite coated filling powder.
[0018] Preferably, in S1, the mass ratio of 2,2'-diallyl bisphenol A to furfural is 12.8-16.4:5.
[0019] Preferably, in S1, the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, with a mass fraction of 25%-45%.
[0020] Preferably, in S2, the molecular weight of NH2-PEG-SH is 2000-6000.
[0021] Preferably, in S2, the mass ratio of NH2-PEG-SH, diallyl bisphenol A furfural resin and tetrahydrofuran is 0.4-0.8:1.3-1.6:10-20.
[0022] Preferably, in S2, the photoinitiator is one of photoinitiator 651, photoinitiator BP, photoinitiator 504, and photoinitiator 784.
[0023] Preferably, in S2, the amount of the photoinitiator added is 3.5%-8.5% of the mass of the diallyl bisphenol A furfural resin.
[0024] Preferably, in S3, the mass ratio of tantalum disilicide powder, coupling agent KH-560 and deionized water is 1:0.14-0.28:10-20.
[0025] Preferably, in S3, the mass ratio of tantalum disilicide epoxide, NH2-PEG-furfural resin and anhydrous ethanol is 1:0.8-1.2:15-25.
[0026] In a second aspect, the present invention provides a method for preparing a water-based peelable coating, comprising the following steps:
[0027] The water-based silicone-modified acrylic emulsion, composite coated filler powder, dispersant and deionized water are weighed according to weight proportions and mixed in a blender, and stirred at a speed of 200-400 r / min for 1 hour. Then, a film-forming aid, a thickener, a leveling agent and a defoaming agent are added, and stirred at a speed of 150-250 r / min for 0.5 hour to obtain a water-based strippable coating.
[0028] The beneficial effects of the present invention are:
[0029] 1. The present invention prepares a water-based peelable coating, which uses water as a solvent and has the advantages of being non-toxic, harmless, and environmentally friendly. By modifying the composite coated filling powder of the coating, not only the hardness of the coating is improved, but also the impact resistance, salt water resistance, and aging resistance of the coating are improved, thereby improving the application effect of the peelable coating.
[0030] 2. The composite coated filling powder prepared by the present invention is firstly subjected to a thiol-double bond click chemical reaction between diallyl bisphenol A furfural resin and amino polyethylene glycol thiol (NH2-PEG-SH) to obtain NH2-PEG-furfural resin containing thioether group and amino group; and then subjected to an epoxy-amino combination reaction with tantalum disilicide epoxide to finally obtain a composite coated filling powder. Among them, tantalum disilicide epoxide is prepared by using tantalum disilicide as a base material and modified by using an epoxy silane coupling agent.
[0031] 3. The diallyl bisphenol A furfural resin used in the preparation of the composite coated filling powder of the present invention is obtained by condensing diallyl bisphenol A and furfural as raw materials under the action of base catalysis to obtain a furfural resin containing diallyl groups, i.e., diallyl bisphenol A furfural resin. Compared with conventional furfural resins, the resin prepared by the present invention contains abundant allyl groups, so that it can participate in subsequent reactions. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0033] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0034] The present invention will be further described below in conjunction with the following examples.
[0035] Example 1
[0036] A water-based strippable coating, calculated by weight, comprising:
[0037] 75 parts of water-based silicone-modified acrylic emulsion, 12 parts of composite coated filler powder, 0.7 parts of dispersant, 1.8 parts of film-forming aid, 0.5 parts of thickener, 0.3 parts of leveling agent, 0.13 parts of defoamer and 15 parts of deionized water.
[0038] The brand of water-based silicone-modified acrylic emulsion is UC-3300, and the manufacturer is Guangzhou Haoyi New Materials Technology Co., Ltd. The dispersant is BYK-191; the film-forming aid is alcohol ester twelve; the thickener is ACRYSOL RM-8W; the leveling agent is BYK-380N; and the defoamer is Dow Corning DC-65.
[0039] The preparation method of the composite coated filling powder comprises:
[0040] S1. Weigh 2,2'-diallyl bisphenol A (DBA) and furfural and add them into a reaction container. The mass ratio of 2,2'-diallyl bisphenol A to furfural is 14.6:5. After fully stirring, add 35% sodium hydroxide solution until the pH value of the reaction solution is 8.5-9.5. Heat to 175° C., keep the temperature under reflux for 3 hours, wash with water three times, and vacuum dry to obtain diallyl bisphenol A furfural resin.
[0041] S2, NH2-PEG-SH (molecular weight is 4000) is added into tetrahydrofuran, after fully dissolving, diallyl bisphenol A furfural resin is added, the mass ratio of NH2-PEG-SH, diallyl bisphenol A furfural resin and tetrahydrofuran is 0.6:1.4:15, stir until uniform, then add a certain amount of photoinitiator 651, the addition amount is 5.5% of the mass of diallyl bisphenol A furfural resin, under the irradiation of 50W ultraviolet light source, stir and react, stirring time is 1.5h, stirring speed is 200r / min, after reaction finishes, remove solvent under reduced pressure, obtain NH2-PEG-furfural resin;
[0042] S3. Weigh 10-20 μm tantalum disilicide powder and mix it with deionized water, add coupling agent KH-560 dropwise, the mass ratio of tantalum disilicide powder, coupling agent KH-560 and deionized water is 1:0.21:15, reflux for 6 hours, filter and dry to obtain tantalum disilicide epoxide; add NH2-PEG-furfural resin to anhydrous ethanol, and then add tantalum disilicide epoxide, the mass ratio of tantalum disilicide epoxide, NH2-PEG-furfural resin and anhydrous ethanol is 1:1:20, heat to 70°C, keep warm and reflux for 4 hours, remove the solvent under reduced pressure to obtain a composite coated filling powder.
[0043] The preparation method of the above-mentioned water-based peelable coating comprises the following steps:
[0044] The water-based silicone-modified acrylic emulsion, composite coated filler powder, dispersant and deionized water were weighed according to weight proportions and mixed in a blender, and stirred at 300 r / min for 1 h. Then, a film-forming aid, a thickener, a leveling agent and a defoaming agent were added, and stirred at 200 r / min for 0.5 h to obtain a water-based strippable coating.
[0045] Example 2
[0046] A water-based strippable coating, calculated by weight, comprising:
[0047] 67 parts of water-based silicone-modified acrylic emulsion, 8 parts of composite coated filler powder, 0.5 parts of dispersant, 1.1 parts of film-forming aid, 0.2 parts of thickener, 0.1 parts of leveling agent, 0.05 parts of defoamer and 10 parts of deionized water.
[0048] The brand of water-based silicone-modified acrylic emulsion is UC-3500, and the manufacturer is Guangzhou Haoyi New Materials Technology Co., Ltd.
[0049] The dispersant is BYK-103; the film-forming aid is propylene glycol butyl ether; the thickener is ACRYSOL RM-12W; the leveling agent is BYK-330; and the defoaming agent is Dow Corning DC-106F.
[0050] The preparation method of the composite coated filling powder comprises:
[0051] S1. Weigh 2,2'-diallyl bisphenol A (DBA) and furfural and add them into a reaction container. The mass ratio of 2,2'-diallyl bisphenol A to furfural is 12.8:5. After fully stirring, add a 25% potassium hydroxide solution until the pH of the reaction solution is 8.5-9.5. Heat to 170° C., keep the temperature under reflux for 2 hours, wash with water three times, and vacuum dry to obtain diallyl bisphenol A furfural resin.
[0052] S2, NH2-PEG-SH (molecular weight is 2000) is added into tetrahydrofuran, after fully dissolving, diallyl bisphenol A furfural resin is added, the mass ratio of NH2-PEG-SH, diallyl bisphenol A furfural resin and tetrahydrofuran is 0.4:1.3:10, stirring until uniform, then adding a certain amount of photoinitiator BP, the addition amount is 3.5% of the mass of diallyl bisphenol A furfural resin, stirring reaction is carried out under the irradiation of a 50W ultraviolet light source, the stirring time is 1h, the stirring speed is 150r / min, after the reaction is completed, the solvent is removed under reduced pressure to obtain NH2-PEG-furfural resin;
[0053] S3. Weigh 10-20 μm tantalum disilicide powder and mix it with deionized water, add coupling agent KH-560 dropwise, the mass ratio of tantalum disilicide powder, coupling agent KH-560 and deionized water is 1:0.14:10, reflux for 3 hours, filter and dry to obtain tantalum disilicide epoxide; add NH2-PEG-furfural resin to anhydrous ethanol, and then add tantalum disilicide epoxide, the mass ratio of tantalum disilicide epoxide, NH2-PEG-furfural resin and anhydrous ethanol is 1:0.8:15, heat to 60°C, keep warm and reflux for 3 hours, remove the solvent under reduced pressure to obtain a composite coated filling powder.
[0054] The preparation method of the above-mentioned water-based peelable coating comprises the following steps:
[0055] The water-based silicone-modified acrylic emulsion, composite coated filler powder, dispersant and deionized water were weighed according to weight proportions and mixed in a blender, and stirred at a speed of 200 r / min for 1 hour. Then, a film-forming aid, a thickener, a leveling agent and a defoaming agent were added, and stirred at a speed of 150 r / min for 0.5 hour to obtain a water-based strippable coating.
[0056] Example 3
[0057] A water-based strippable coating, calculated by weight, comprising:
[0058] 84 parts of water-based silicone-modified acrylic emulsion, 16 parts of composite coated filler powder, 1 part of dispersant, 2.3 parts of film-forming aid, 0.8 parts of thickener, 0.5 parts of leveling agent, 0.2 parts of defoamer and 20 parts of deionized water.
[0059] The brand of water-based silicone-modified acrylic emulsion is UC-3300, and the manufacturer is Guangzhou Haoyi New Materials Technology Co., Ltd.
[0060] The dispersant is BYK-810; the film-forming aid is propylene glycol methyl ether acetate; the thickener is ACRYSOL RM-12W; the leveling agent is BYK-333; and the defoaming agent is Dow Corning ACP-1400.
[0061] The preparation method of the composite coated filling powder comprises:
[0062] S1. Weigh 2,2'-diallyl bisphenol A (DBA) and furfural and add them into a reaction container. The mass ratio of 2,2'-diallyl bisphenol A to furfural is 16.4:5. After fully stirring, add a 45% sodium hydroxide solution until the pH value of the reaction solution is 8.5-9.5. Heat to 180° C., keep the temperature under reflux for 3 hours, wash with water three times, and vacuum dry to obtain diallyl bisphenol A furfural resin.
[0063] S2, NH2-PEG-SH (molecular weight is 6000) is added into tetrahydrofuran, after fully dissolving, diallyl bisphenol A furfural resin is added, the mass ratio of NH2-PEG-SH, diallyl bisphenol A furfural resin and tetrahydrofuran is 0.8:1.6:20, stir until uniform, then add a certain amount of photoinitiator 504, the addition amount is 8.5% of the mass of diallyl bisphenol A furfural resin, under the irradiation of 50W ultraviolet light source, stir and react, stirring time is 2h, stirring speed is 200r / min, after reaction finishes, remove solvent under reduced pressure, obtain NH2-PEG-furfural resin;
[0064] S3. Weigh 10-20 μm tantalum disilicide powder and mix it with deionized water, add coupling agent KH-560 dropwise, the mass ratio of tantalum disilicide powder, coupling agent KH-560 and deionized water is 1:0.28:20, reflux for 8 hours, filter and dry to obtain tantalum disilicide epoxide; add NH2-PEG-furfural resin to anhydrous ethanol, and then add tantalum disilicide epoxide, the mass ratio of tantalum disilicide epoxide, NH2-PEG-furfural resin and anhydrous ethanol is 1:1.2:25, heat to 80°C, keep warm and reflux for 6 hours, remove the solvent under reduced pressure to obtain a composite coated filling powder.
[0065] The preparation method of the above-mentioned water-based peelable coating comprises the following steps:
[0066] The water-based silicone-modified acrylic emulsion, composite coated filler powder, dispersant and deionized water were weighed according to weight proportions and mixed in a blender, and stirred at 400 r / min for 1 h. Then, a film-forming aid, a thickener, a leveling agent and a defoaming agent were added, and stirred at 250 r / min for 0.5 h to obtain a water-based strippable coating.
[0067] Comparative Example 1
[0068] A water-based strippable coating, which differs from Example 1 in that the composite coated filling powder is replaced with tantalum disilicide powder, and the other ingredients and methods remain unchanged.
[0069] Comparative Example 2
[0070] A water-based strippable coating, which differs from Example 1 in that the composite coated filler powder is replaced with diallyl bisphenol A furfural resin (prepared in the same way as Example 1), and the other components and methods remain unchanged.
[0071] Comparative Example 3
[0072] A water-based strippable coating, which differs from Example 1 in that the composite coated filler powder is replaced by a mixture of tantalum disilicide powder and diallyl bisphenol A furfural resin (prepared in the same way as in Example 1), the mass ratio of tantalum disilicide powder to diallyl bisphenol A furfural resin is 1:1.4, and the other ingredients and methods remain unchanged.
[0073] Experimental testing
[0074] The properties of the coatings prepared in Example 1 and Comparative Examples 1-3 were tested. The coating was first sprayed on a 304 stainless steel plate with a spraying thickness of 100 μm. After drying at room temperature for 7 days, the surface hardness (refer to GB / T6739-2006), impact resistance (refer to GB / T 1732-2020), aging resistance (irradiated with ultraviolet light at a power of 100 W for 500 h, and observed whether shedding or powdering occurred) and salt water resistance (immersed in a 3% sodium chloride solution for 72 h, and observed whether bubbling occurred) of the coating were tested.
[0075] The results are shown in Table 1:
[0076] Table 1 Performance test results of different coatings
[0077]
[0078] It can be seen from Table 1 that the coating prepared in Example 1 of the present invention has higher surface hardness, better impact resistance, and better salt water resistance and aging resistance. It can be used in more severe environmental conditions, greatly increasing the scope of application.
[0079] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0080] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A water-based peelable coating, characterized in that: Calculated by weight, including: 67-84 parts of water-based silicone-modified acrylic emulsion, 8-16 parts of composite coated filler powder, 0.5-1 parts of dispersant, 1.1-2.3 parts of film-forming aid, 0.2-0.8 parts of thickener, 0.1-0.5 parts of leveling agent, 0.05-0.2 parts of defoamer and 10-20 parts of deionized water; The preparation method of the composite coated filling powder comprises: S1. Weigh 2,2'-diallyl bisphenol A and furfural into a reaction container, stir thoroughly, add alkali solution until the pH of the reaction solution is 8.5-9.5, heat to 170-180°C, keep the temperature under reflux for 2-3h, wash with water three times, and vacuum dry to obtain diallyl bisphenol A furfural resin; S2, adding NH2-PEG-SH into tetrahydrofuran, after fully dissolving, then adding diallyl bisphenol A furfural resin, stirring until uniform, then adding a certain amount of photoinitiator, stirring reaction under irradiation of ultraviolet light, stirring time is 1-2h, stirring speed is 150-200r / min, after the reaction is completed, removing the solvent under reduced pressure to obtain NH2-PEG-furfural resin; S3. Weigh tantalum disilicide powder and deionized water, add coupling agent KH-560 dropwise, reflux for 5-8 hours, filter and dry to obtain tantalum disilicide epoxide; add NH2-PEG-furfural resin to anhydrous ethanol, then add tantalum disilicide epoxide, heat to 60-80°C, keep warm and reflux for 3-6 hours, remove the solvent under reduced pressure to obtain a composite coated filling powder.
2. A water-based peelable coating according to claim 1, characterized in that: The dispersant is at least one of BYK-191, BYK-103 and BYK-810; the film-forming aid is at least one of alcohol ester dodecanol, propylene glycol butyl ether and propylene glycol methyl ether acetate.
3. A water-based peelable coating according to claim 1, characterized in that: The thickener is at least one of ACRYSOL RM-8W, ACRYSOL RM-12W, and ADEKANOL UH-420.
4. A water-based peelable coating according to claim 1, characterized in that: The leveling agent is at least one of BYK-380N, BYK-330, BYK-333, and BYK-350.
5. A water-based peelable coating according to claim 1, characterized in that: The defoaming agent is at least one of Dow Corning DC-65, Dow Corning DC-106F, Dow Corning ACP-1400 and Dow Corning AFE-1247.
6. A water-based peelable coating according to claim 1, characterized in that: In S1, the mass ratio of 2,2'-diallyl bisphenol A to furfural is 12.8-16.4:5; the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution, and the mass fraction is 25%-45%.
7. A water-based peelable coating according to claim 1, characterized in that: In the S2, the molecular weight of NH2-PEG-SH is 2000-6000; the mass ratio of NH2-PEG-SH, diallyl bisphenol A furfural resin and tetrahydrofuran is 0.4-0.8:1.3-1.6:10-20.
8. A water-based peelable coating according to claim 1, characterized in that: In S3, the mass ratio of tantalum disilicide powder, coupling agent KH-560 and deionized water is 1:0.14-0.28:10-20; the mass ratio of epoxidized tantalum disilicide, NH2-PEG-furfural resin and anhydrous ethanol is 1:0.8-1.2:15-25.
9. A method for preparing the water-based peelable coating according to claim 1, characterized in that: The following steps are involved: The water-based silicone-modified acrylic emulsion, composite coated filler powder, dispersant and deionized water are weighed according to weight proportions and mixed in a blender, and stirred at a speed of 200-400 r / min for 1 hour. Then, a film-forming aid, a thickener, a leveling agent and a defoaming agent are added, and stirred at a speed of 150-250 r / min for 0.5 hour to obtain a water-based strippable coating.
Citation Information
Patent Citations
Water-based strippable anticorrosive paint and preparation method thereof
CN112521819A
High-emissivity self-healing silicone rubber lightweight ablation-resistant thermal insulation coating
CN113801573A